2022
DOI: 10.2340/17453674.2022.3038
|View full text |Cite
|
Sign up to set email alerts
|

Rate of conversion to secondary arthroplasty after femoral neck fractures in 796 younger patients treated with internal fixation: a Swedish national register-based study

Abstract: Background and purpose: In younger patients with a femoral neck fracture (FNF), internal fixation is the recommended treatment regardless of displacement. Healing complications are often treated with arthroplasty. We determined the rate of conversion to arthroplasty up to 5 years after fixation of either undisplaced FNFs (uFNFs) or displaced FNFs (dFNFs).Patients and methods: The study was based on prospectively collected data from the Swedish Fracture Register (SFR) and the Swedish Arthroplasty Register (SAR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Our study is the first to combine the ONFH-related findings on conventional radiography and MARS MRI and compare them with PROs after FNF. We consider our cohort to represent the most relevant age group for this study, as FNFs in this age group are treated primarily with internal fixation (2).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is the first to combine the ONFH-related findings on conventional radiography and MARS MRI and compare them with PROs after FNF. We consider our cohort to represent the most relevant age group for this study, as FNFs in this age group are treated primarily with internal fixation (2).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Osteonecrosis of the femoral head (ONFH) is a well-known complication after internal fixation of a femoral neck fracture (FNF) (1). For young patients and patients with undisplaced fractures, internal fixation is still the most common treatment (2). Development of ONFH can be devastating, leading to pain, disability, and need for secondary surgery (3,4).…”
mentioning
confidence: 99%
“…In most patients current evidence cannot detect any differences of clinical importance between THA and HA approaches [ 15 ]. Notable is the high age cut-off (60 to 70 years) [ 16 , 17 ] in Scandinavia for using IF for displaced FNFs. Thus, many healthy “young old” will undergo IF rather than (total) arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anatomic reduction and compression is paramount to promote successful primary bone healing because these injuries are associated with high complication rates including avascular necrosis and nonunion rates of 8% to 23%. [3][4][5][6] Reduction quality in the treatment of these injuries has been emphasized since the onset of their operative management. Studies have demonstrated worse fracture reduction is associated with poorer outcomes 5,[7][8][9] .…”
mentioning
confidence: 99%
“…Therefore, anatomic reduction and compression is paramount to promote successful primary bone healing because these injuries are associated with high complication rates including avascular necrosis and nonunion rates of 8% to 23%. 3-6…”
mentioning
confidence: 99%